Single Cell Electrochemiluminescence Analysis of Cholesterol in Plasma Membrane during Testosterone Treatment. Issue 5 (7th January 2020) - Li, Linyu; Liu, Kang; Fang, Danjun
Abstract: The fluctuation of cholesterol in plasma membrane at single cells during testosterone treatment was evaluated using luminol electrochemiluminescence at the first time. Testosterone over the human physiological concentration induced more membrane cholesterol that was associated with upregulated cholesterol synthesis inside the cells. However, the evaluation at single cell level revealed some individual cells with similar membrane cholesterol, while the other individual cells with more membrane cholesterol after the treatment. The observation of non‐responsive cells to testosterone treatment exhibited the heterogeneous cellular function during this process, which should provide more information to understand the side effects of testosterone replacement therapy. Abstract :